Evaluation of the Traditional Health Services Implementation at Kudus Regency Health Center - Amaliana, Tri Vera; Laksono, Budi; Rahayu, Sri Ratna (Universitas Negeri Semarang, 2021)
Traditional health service is a medication or treatment based on the empirically hereditary experience and expertise. The phenomenon of using traditional health services implies the responsibility of health and law. This research aims to evaluate the implementation of traditional health services in Kudus Regency Health Center in 2019. This research is a qualitative study, the selection of informants is determined with purposive sampling technique and then to complete the information is by snowball sampling. The method uses to collect the data is a deep interview with the health workers of the health center that had gotten training on traditional health, the head of the health center, and officers of the Kudus Public Health Office. The result of the research shows that the implementation of traditional health services in Kudus Health Center is not optimal yet. This is due to the limited human resources providing traditional health services, the lack of space to provide the traditional health service, and there is no policy from the government regarding the traditional health service.